Kekuatan Hukum Pembuktian Kontrak Elektronik dalam Transaksi Digital Perbankan Syariah - Barus, Utary Maharani; Azwar, T. Keizerina Devi; Yuswar, Cheryl Patriana; Nasution, Siti Nurahmi; Wau, Hilbertus Sumplisius (Faculty of Law, Andalas University, 2024)
This paper aims to obtain an overview of the validity of electronic contracts, the execution of electronic contract by Shariah banks, and the legal force of proof of the electronic contract in digital shariah banking transactions. To achieve these goals, this research uses a normative legal writing with descriptive-analytical specifications. The findings reveal, first, in the perspective of Islamic law in Indonesia, electronic contracts are valid as long as they comply with the general principles of Shariah. Second, this reserach conducted a Focus Group Discussion with two Sharia banks namely Bank Mega Shariah Deli Serdang and Bank Muamalat Jakarta in order to obtain results related to how the execution of electronic contracts on both shariah banks. The result is that PT Mega Bank Shariah Deli Serdang has performed various consumer services based on digital, but not yet for electronic contracts based on financing. The absence of the electronic contract for this financing because it still needs a direct and face-to-face agreement with a notary. Along with its colleague, Bank Muamalat has not yet implemented electronic contracts for financing. Whenever there is an electronic contract that Bank Muamalat is conducted, namely E-Akad in Hajj planning program and E-akad in the value chain system program.. For the two types of e-contract such, Bank Muamalat has never had a dispute with the customer so these two shariah banks have never experienced proof of electronic contract in the trial. Thirdly, theoretically, electronic contracts have been recognised as legitimate evidence in Indonesian law. However, implementation on the ground shall take into account certain terms and conditions.